Evaluation of the expression of Bmi-1 stem cell marker in sinonasal melanomas and its correlation with the expression of cell cycle proteins - Harim Tavares dos Santos; Juliana de Souza do Nascimento; Fernanda Meireles; João Figueira Scarini; Erika Said Egal; Victor Angelo Montalli; Felipe Paiva Fonseca; Fernanda Viviane Mariano; Albina Altemani (BMC, 2019)
Abstract Background Sinonasal melanomas (SNM) are aggressive neoplasms, which present distinct clinicopathological and molecular aspects when compared to cutaneous melanomas (CM). B-cell-specific moloney murine leukemia virus integration site-1 (Bmi-1) is a stem cell marker involved in the regulation of the cell cycle and has been found to be expressed in 70% of CM and 100% of benign nevi. Regarding the cell cycle, Bmi-1 is known to be an upstream repressor of p16, which is a tumor suppressor encoded by the INK4a/Arf locus. Considering this, the aim of this study is to evaluate the immunohistochemical expression of Bmi-1 in a series of SNM and its correlation with the expression of cell cycle proteins (p16 and Ki-67, a nuclear antigen of proliferating cells). Methods In 16 cases of SNM, nuclear expression of Bmi-1 and nuclear and cytoplasmic of p16 was classified as: absent, low (> 5 to < 50% of cells) and high (≥50%). Ki-67 proliferation index was represented by the ratio positive cells/ total cells. Results Histologically, all cases presented varying amount of necrosis and 75% contained undifferentiated cells. Bmi-1 was detected in 6 cases (37.5%) with high level of expression in 2; p16 expression was seen in 10 cases (62.5%) with high level in 7. The frequency of p16 expression did not differ significantly between tumors with or without Bmi-1 expression. Ki-67 index ranged from 8 to 22%. Neither Bmi-1 nor p16 expression showed correlation with Ki-67 index. Bmi-1 negative tumors presented more extensive necrosis (71.4%); no association between Bmi-1 expression and undifferentiated phenotype was observed. Conclusions In our SNM series, low immunohistochemical expression of Bmi-1 was a common phenomenon favoring the hypothesis that mucosal melanoma possibly presents molecular pathways different from the cutaneous counterpart. In SNM, Bmi-1 and p16 expression levels did not correlate with each other or with the cell proliferative index.